Applications of Rietveld-based QXRD analysis in mineral processing. Issue 1 (17th November 2014) - Li, Jian; McDonald, Robbie G.; Kaksonen, Anna H.; Morris, Christina; Rea, Suzy; Usher, Kayley M.; Wylie, Jason; Hilario, Felipe; du Plessis, Chris A.
<x content-type="archive" xml:space="preserve">Abstract</x> Rietveld-based quantitative X-ray diffraction (QXRD) has been extensively used for mineralogical characterization in order to understand the reaction chemistry, and kinetics of minerals leaching and formation. This work presents examples where QXRD has been applied to understanding fundamental aspects of these two processes. Firstly, the co-processing of nickel laterites and sulphidic materials has the potential to offer several advantages that include the use of lower grade (including non-smeltable) concentrates, improvement in the rheological behaviour of the blends, and reduction in the use of sulphuric acid. The leaching kinetics and chemistry of mixed nickel laterite ore and sulphide concentrate were explored by the QXRD analysis of feed materials and, intermediates and final leach residues produced using controlled oxidation rates. Under high temperature (250 °C) and pressure oxidation ( 40 to 45 atm.) conditions, sulphide minerals in the nickel concentrate underwent several oxidative hydrothermal transformations, and ferrous iron was oxidized and precipitated primarily as hematite. High recovery of nickel can be achieved with low acid consumption under these conditions. Secondly, iron precipitation/removal is an important down-stream process in hydrometallurgy. Moderate concentrations of ferrous iron can be oxidized using micro-organisms with oxidation rates several orders of magnitude faster compared with abiotic oxidation at ambient temperature and pressure. QXRD and chemical analysis have indicated that after oxidation, iron at pH 2 mostly precipitates as jarosite with various amounts of K+, Na+, NH4+, and H3O+ incorporated into the structure. Bio-catalysed iron removal can be achieved with minimum copper and nickel losses at relatively low pH conditions.